Analysis of polymer viscoelastic properties based on compressive creep tests during hot embossing for two‐dimensional polyethylene terephthalate nanochannels. Issue 10 (29th October 2013) - Yin, Zhifu; Cheng, E; Zou, Helin; Jurčíček, Petr
<x xml:space="preserve">Abstract</x> Hot embossing is an emerging technology, which enables cost‐effective and high‐productivity nanofabrication. It is important to optimize the processing parameters to achieve high replication accuracy nanostructure fabrication. In this article, to reveal the interrelationship between the hot embossing conditions and replication accuracy of two‐dimensional (2D) polyethylene terephthalate (PET) nanochannels, the numerical simulations were conducted by using the generalized Maxwell model. The constants of the generalized Maxwell model were calculated by a newly established fitting formula based on experimental compressive creep curves rather than tensile stress relaxation curves. Replication accuracy of 2D PET nanochannels was evaluated by a method based on weighted averages. Orthogonal method was employed during numerical simulations to optimize the hot embossing process. Under optimized hot embossing parameters, 2D PET nanochannels, ∼80 nm wide, 250 nm deep and 4 mm long, were precision‐imprinted into a PET sheet. POLYM. ENG. SCI., 54:2398–2406, 2014. © 2013 Society of Plastics Engineers